2018
DOI: 10.1007/s00018-018-2958-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in ovarian cancer cells by miR-493-3p directly targeting AKT2, STK38L, HMGA2, ETS1 and E2F5

Abstract: The results published here are based upon data generated by the TCGA Research Network. In addition, the authors are grateful to Dr. Anne-Marie Mes-Masson (Centre Hospitalier de l´Université de Montréal, Canada) for providing us with the TOV21G and TOV112D cells as well as to Alex Shu-Wing Ng (Department of Obstetrics, Gynecology and Reproductive Biology, the Brigham and Women's Hospital, Boston, USA) for the HOSE 2170 cells. The OVCAR3, A2780 and A2780-cis cells were kindly provided by Verena Jendrossek (Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…8,20,27,28 Intriguingly, studies have noted that KDM3A could control the transcriptional activation of ETS1 in a similar manner. 9,29 ETS1 has been noted as an important oncogene and a treating target in multiple malignancies including breast cancer, 30,31 ovarian cancer, 32,33 and CC as well. 11,34 To validate this potential interaction between KDM3A and ETS1, we first identified nuclearlocalization of KDM3A and ETS1 in CC cells, and then a positive correlation between KDM3A and ETS1 was identified.…”
Section: Discussionmentioning
confidence: 99%
“…8,20,27,28 Intriguingly, studies have noted that KDM3A could control the transcriptional activation of ETS1 in a similar manner. 9,29 ETS1 has been noted as an important oncogene and a treating target in multiple malignancies including breast cancer, 30,31 ovarian cancer, 32,33 and CC as well. 11,34 To validate this potential interaction between KDM3A and ETS1, we first identified nuclearlocalization of KDM3A and ETS1 in CC cells, and then a positive correlation between KDM3A and ETS1 was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggested that miR-493 inhibits the biological behavior of lung tumor [14]. Meanwhile, miR-493 also acts as a suppressor in various cancers including colon cancer, bladder cancer, and ovarian cancer via multiple intracellular signaling pathways [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…20 E2F5 was upregulated in OC, and E2F5 promoted cell proliferation, mobility, and induced apoptosis. [20][21][22] Moreover, the data showed that miR-1271-5p suppressed E2F5 to inhibit OC progression. 23 These data indicated that E2F5 was a positive regulator for the development of OC.…”
Section: Introductionmentioning
confidence: 99%